Maskless Fabrication of Film-Patterned-Retarder (FPR) Using Wedged Liquid Crystal Cell - Doyeon Lee; Keumcheol Kwak; Chul Gyu Jhun; Hyun Seok Choi; Jang-kun Song (IEEE Photonics Journal, 2019)
Film-patterned-retarder (FPR) is an optical film used in the stereoscopic 3D display and is fabricated using an expensive photomask and nano-wire grid polarizer. This method is expensive and the pitch of FPR is fixed for a given photomask. Here, we introduce a maskless fabrication method for FPR using a wedged liquid crystal (LC) cell. The retardation of the wedged LC cell is continuously increased from one edge to the other. When the polarized monochromatic laser beam (450 nm) passes through the cell, periodically undulated polarization pattern of light is obtained, and can be used to produce FPR by combining with the photo-alignment method. The method does not require the expensive photomask and nano-wire grid polarizer, and the pitch of FPR can be simply controllable by changing the birefringence of LC material with temperature or using a light source of different wavelengths. Thus, this method can provide a simple and cost-effective method for FPR fabrication.